2023
DOI: 10.1021/acs.jpclett.3c01654
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Proton Transfer and Contact Ion-Pair Formation in Formic Acid Clusters

Shaun F. Sutton,
Chase H. Rotteger,
Carter K. Jarman
et al.

Abstract: The ultrafast proton transfer dynamics of homogeneous formic acid clusters (FA) n , n < 10, are investigated with femtosecond time-resolved mass spectrometry. We monitor the proton transfer pathway following Rydberg state electronic relaxation and find that successful ion pair formation increases logarithmically with cluster size. Ab initio calculations demonstrate similar excitation/relaxation behavior for each cluster, revealing a contact ion pair forms between two molecules composing the cluster before fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…[41][42][43][44][45] The proton transfer reaction and contact ion pair formation after electron excitation into Rydberg states in formic acid clusters was investigated by ultrafast time-resolved mass spectrometry. [46] With substantial concentrations of formic acid in the atmosphere, [47][48][49] special emphasis has been placed on studying FA hydration in water clusters, such as identifying the minimum energy structures and binding energies. [50][51][52][53][54] Other processes emerge upon hydration, notably FA ionic dissociation, predicted for neutral FA • W N clusters with N � 8 water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44][45] The proton transfer reaction and contact ion pair formation after electron excitation into Rydberg states in formic acid clusters was investigated by ultrafast time-resolved mass spectrometry. [46] With substantial concentrations of formic acid in the atmosphere, [47][48][49] special emphasis has been placed on studying FA hydration in water clusters, such as identifying the minimum energy structures and binding energies. [50][51][52][53][54] Other processes emerge upon hydration, notably FA ionic dissociation, predicted for neutral FA • W N clusters with N � 8 water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…performed direct ab initio molecular dynamics (AIMD) and suggested that the FA dimer cation could form a complex, where the carbonyl oxygen atom was bound symmetrically leading to the formation of a face-to-face complex. However, with increasing temperature, a proton transferred H + (HCOOH)-HCO 2 radical cation would be dominant with a 78% formation probability at room temperature, and absent at 0 K. Very recently, Sutton et al, using ultrafast time-resolved pump–probe mass spectrometry, monitored the proton transfer pathway following Rydberg state excitation for a series of FA clusters . A contact ion-pair mechanism was shown to be operational leading finally to a protonated FA cluster and the HCOO – anion.…”
Section: Introductionmentioning
confidence: 99%